Prevalence of Congenital Heart Disease and Associated Factors among Infants with Myelomeningocele: A cross-sectional study - Mohammed Nasir; Bereket Tessema; Sura Markos (PLoS ONE, 2026)
Background Meningomyelocele (MMC) is believed to commonly coexist with congenital heart disease (CHD), due to embryological pathways involving neural crest cells and risk factors such as folate and homocysteine metabolism abnormalities. However, evidence from developing countries is limited. Therefore, this study assessed the prevalence of CHD among infants with MMC and identified factors associated with the occurrence of CHD in infants with MMC. Methodology This hospital-based cross-sectional study was conducted at Hawassa University Comprehensive Hospital between May 1 and August 1, 2025. Infants with MMC born from January 1, 2018, to January 1, 2024, who underwent echocardiographic evaluation were included. Data were collected through chart review. Prevalence of CHD in infants with MMC was described using frequencies and percentages, and binary logistic regression identified factors associated with CHD. Results A total of 265 infants with MMC were included in this study. The prevalence of CHD among infants with MMC was 7.2%. The presence of maternal history of spontaneous abortion [AOR = 2.51, (95% CI: 1.12, 9.83); P = 0.03], maternal overweight or obesity [AOR = 2.93, (95% CI: 1.15, 7.98); P = 0.01], maternal diabetes mellitus [AOR = 2.22, (95% CI: 1.13, 8.45); P = 0.01], extracardiac anomalies in the infant [AOR = 2.94, (95% CI: 1.11, 8.78); P = 0.04] were associated with CHD in infants with MMC. Conclusion CHD was relatively common among infants with MMC, affecting 7.2% of cases. Factors associated with CHD included maternal history of spontaneous abortion, maternal overweight or obesity, maternal diabetes mellitus, and the presence of extracardiac anomalies in the infant. These findings highlight the significance of routine cardiac evaluation and targeted maternal risk assessment in infants with MMC to improve early detection and management.